2015
DOI: 10.1016/j.jacc.2014.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Revascularization of Chronic Hibernating Myocardium Stimulates Myocyte Proliferation and Partially Reverses Chronic Adaptations to Ischemia

Abstract: Background The time course and extent of recovery after revascularization of viable dysfunctional myocardium is variable. While fibrosis is a major determinant, myocyte structural and molecular remodeling may also play important roles. Objective This study sought to determine whether persistent myocyte loss and/or irreversibility of protein changes that develop in hibernating myocardium have an impact on functional recovery in the absence of infarction. Methods Swine instrumented with a chronic left anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…This may explain the greater improvement in WT% and SRS% with PQS. Consistent with previous studies [18,29], myocyte nuclear density was increased by PQS. Treatment with PQS attenuated the cellular hypertrophy, indicating that PQS improve oxygen transport across the sarcolemma in the ischemic myocardium [30].…”
supporting
confidence: 93%
“…This may explain the greater improvement in WT% and SRS% with PQS. Consistent with previous studies [18,29], myocyte nuclear density was increased by PQS. Treatment with PQS attenuated the cellular hypertrophy, indicating that PQS improve oxygen transport across the sarcolemma in the ischemic myocardium [30].…”
supporting
confidence: 93%
“…This could reflect the time course of these markers prior to tissue harvesting as well as variations in the time over which cells are Ki67 or pHH3 positive with each treatment. Recent studies have demonstrated that physiological stimuli such as revascularization itself can also stimulate cardiac repair and alter these myocyte proliferation indices 45 . Regardless of the proliferative indices measured at a single time point (which reflect a rate of myocyte division at that point in time), the increase in nuclear density and reduction in myocyte size assessed 4-weeks after treatment reflects the cumulative myocyte increase which was the same with icMSCs and icCDCs.…”
Section: Discussionmentioning
confidence: 99%
“…[18,19] In humans, proliferation may stall due to persistent hypoxia or limited energetic substrate. [20,21] Following revascularisation, cardiomyocyte re-differentiation and proliferation has been observed, which may underlie functional recovery [22].…”
Section: Pathophysiology Of Hibernating Myocardiummentioning
confidence: 99%